Proposal to use superparamagnetic nanoparticles to test the role of cryptochrome in magnetoreception - Worster, S; Hore, P (Royal Society, 2018)
Evidence is accumulating to support the hypothesis that some animals use light‐induced radical pairs to detect the direction of the Earth’s magnetic field. Cryptochrome proteins seem to be involved in the sensory pathway but it is not yet clear if they are the magnetic sensors: they could, instead, play a non‐magnetic role as signal transducers downstream of the primary sensor. Here we propose an experiment with the potential to distinguish these functions. The principle is to use superparamagnetic nanoparticles to disable any magnetic sensing role by enhancing the electron spin relaxation of the radicals so as to destroy their spin correlation. We use spin dynamics simulations to show that magnetoferritin, a synthetic, protein‐based nanoparticle, has the required properties. If cryptochrome is the primary sensor, then it should be inactivated by a magnetoferritin particle placed 12‐16 nm away. This would prevent a bird from using its magnetic compass in behavioural tests and abolish magnetically sensitive neuronal firing in the retina. The key advantage of such an experiment is that any signal transduction role should be completely unaffected by the tiny magnetic interactions (<< kBT ) required to enhance the spin relaxation of the radical pair.